The alteration of media: A veces cubierto por las aguas by Carlos Cociña - Apablaza, Pablo (Revista Chilena de Literatura, 2021)
In this article I intend to explore the publication media of the poem A veces cubierto por las aguas by Carlos Cociña. This work was published in 2003 on the Poesía Cero website. In 2013, it was included in the anthology El margen de la propia vida, printed on single pages inside an envelope, and, in 2015, it was presented along with Orchestra of Poets, in the context of a public and performative reading. From digital to printed and from print to reading, I am interested in analyzing the random nature of A veces cubierto por las aguas, considering the scriptural procedures of potentiality and restriction outlined by the Oulipo group. In short, these resources establish a link with the poetics of Cociña’s work and the dematerialization of the publication supports (web page, printed book, and performance).